Main campus - Looking southeast at cubical units A-Z and classrooms 1-16 (1950)
Caption reads: 'Temporary pre-fab metal classroom buildings. Twenty of these units are equipped and used as lecture classrooms. An additional 20 are distributed over the campus and are used to supplement existing laboratories.'